Advances in vinegar production - Bekatorou, Argyro (Boca Raton : CRC Press, 2020)
In industrial vinegar production, there are three main types of methods involved; the slow, handcrafted, traditional method ("Orleans" or "French" method), and the rapid submerged and generator methods. The current trend is to fuse traditional techniques with state-of-the-art technologies, and a variety of approaches have been developed to increase fermentation efficiency and reduce cost and fermentation time. This book reports on all the recent innovations in vinegar production, and compares them to the traditional submerged fermentation systems. The new trends on raw materials, substrate pretreatment strategies, alcoholic fermentation, and acetitification systems are also reviewed.
Chapter 1. History and Current Issues of Vinegar. Chapter 2. Types of Vinegars, Chapter 3. The Biochemistry of Vinegar Production. Chapter 4. Advances in Enumeration and Identificationof Vinegar Cultures. Chapter 5. Raw Materials and Pretreatment Methods for Vinegar Production. Chapter 6. Current Industrial Vinegar Production: Acetators, Processes, and Consumables. Chapter 7. Advances in Immobilized Biocatalyst Technologies for Vinegar Production. Chapter 8. Solid-State Fermentation systems for Vinegar Production. Chapter 9. Current Trends in Balsamic/Aged Vinegar Production and Research. Chapter 10. Vinegar Production in China. Chapter 11. Current Aspects of Wine/Raisin Vinegar Production and Fields of Improvement. Chapter 12. Cider Vinegar Production. Chapter 13. Vinegars Made with Kefir. Chapter 14. Innovative Vinegar Products. Chapter 15. Modeling and Optimization of Acetic Acid Fermentation. Chapter 16. Post-Fermentation Treatments of Vinegars. Chapter 17. Vinegar Aroma Profile aand Analysis. Chapter 18. Health Benefits of Vinegars. Chapter 19. Dilution Water in the Vinegar Industry. Chapter 20. Rapid Detection Methods for Online Monitoring of Vinegar Fermentations. Chapter 21. Fraud, Quality, and Methods for Characterization and Authentication of Vinegars. Chapter 22. Life Cycle Assessment in the Vinegar Sector.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Food Science; Vinegar; Vinegar industry